Answer:
b. Multiply 15 by 9, then divide by 2
Step-by-step explanation:
15 / 2/9 = 15 * 9/2
Answer: b. Multiply 15 by 9, then divide by 2
Let 'a' be the number of ounces of 2%-solution in the 25-ounce mixture
and 'b' be the number of ounces of 5%-solution in the 25-ounce mixture.
Since, fluid ounces of each concentration should be combined to make 25 fl oz.
So, a+b=25 (Equation 1)
And, a container of 2% acid solution and a container of 5% acid solution should be combined to make 25 fl oz of 3.2% acid solution.
So, a of 2% + b of 5% = 3.2% of 25
![(a \times \frac{2}{100})+(b \times \frac{5}{100})= 25 \times \frac{3.2}{100}](https://tex.z-dn.net/?f=%20%28a%20%5Ctimes%20%5Cfrac%7B2%7D%7B100%7D%29%2B%28b%20%5Ctimes%20%5Cfrac%7B5%7D%7B100%7D%29%3D%2025%20%5Ctimes%20%5Cfrac%7B3.2%7D%7B100%7D%20)
![(0.02a)+(0.05b)= 0.8](https://tex.z-dn.net/?f=%20%280.02a%29%2B%280.05b%29%3D%200.8%20)
Multiplying the above equation by 100, we get
(Equation 2)
Substituting the value of a=25-b in equation 2, we get
![2(25-b)+5b=80](https://tex.z-dn.net/?f=%202%2825-b%29%2B5b%3D80%20)
![50-2b+5b=80](https://tex.z-dn.net/?f=%2050-2b%2B5b%3D80%20)
![50+3b=80](https://tex.z-dn.net/?f=%2050%2B3b%3D80%20)
![3b=30](https://tex.z-dn.net/?f=%203b%3D30%20)
![b=10](https://tex.z-dn.net/?f=%20b%3D10%20)
Since, a=25-b
a= 25-10
a=15.
So, 15 fluid ounces of 2% solution combined with 10 ounces of the 5% solution to create a 25-ounce mixture at 3.2% concentration of acid.
The answer is C
4(3-x)+6x=3x+12-x All real numbers are solutions.
<u>The possible answers are:
</u><u /><u /><u><em /></u>4.21
4.22
4.23
4.24
Explanation:
We want a number between 4 1/5 and 4.25. We will convert 4 1/5 to a decimal first:
Divide 1 by 5: 1/5 = 0.2.
This makes 4 1/5 = 4 + 1/5 = 4 + 0.2 = 4.2.
We want a number between 4.2, which can be written as 4.20, and 4.25. Any number between will do, so the possible answers would be
4.21, 4.22, 4.23, or 4.24.<u />
Answer:
x= -12
Step-by-step explanation:
Simplifying
4x + 10 = 2x + -14
Reorder the terms:
10 + 4x = 2x + -14
Reorder the terms:
10 + 4x = -14 + 2x
Solving
10 + 4x = -14 + 2x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-2x' to each side of the equation.
10 + 4x + -2x = -14 + 2x + -2x
Combine like terms: 4x + -2x = 2x
10 + 2x = -14 + 2x + -2x
Combine like terms: 2x + -2x = 0
10 + 2x = -14 + 0
10 + 2x = -14
Add '-10' to each side of the equation.
10 + -10 + 2x = -14 + -10
Combine like terms: 10 + -10 = 0
0 + 2x = -14 + -10
2x = -14 + -10
Combine like terms: -14 + -10 = -24
2x = -24
Divide each side by '2'.
x = -12
Simplifying
x = -12